Empowering MSMEs Through Community-Based QRIS Implementation: A Case Study In Susukan District, East Jakarta - Talitha, Devita Ranaa; Faradysa, Ananda Lingga; Pinandita, Agung Syukroni; Rahmawati, Lidya; Susanti, Eka Nana (Jurnal Pengabdian Masyarakat, 2025)
Purpose: This study addresses the challenge of digital transformation for MSMEs in urban Indonesia, focusing on low digital literacy and limited technology access in Susukan Village, East Jakarta. It aims to enhance MSME capacity through community-based QRIS implementation, promoting financial inclusion and business competitiveness. Method: A participatory action approach was used, involving observation, training, mentoring, and evaluation with eight selected MSMEs. Data were collected via interviews, direct observation, and activity logs, then analyzed using qualitative descriptive methods and data triangulation. Practical Applications: Findings support scalable models for local digital empowerment, benefiting policymakers, educators, and communities in improving digital payment adoption and marketing practices among MSMEs. Conclusion: The program significantly improved digital skills and QRIS adoption, demonstrating that context-sensitive, educational interventions foster sustainable digital inclusion and economic resilience at the grassroots level.